Estimating hysteresis effects - Francesco Furlanetto; Antoine Lepetit; Ørjan Robstad; Juan Francisco Rubio-Ramírez; Pål Ulvedal (Federal Reserve Bank of Atlanta, 2021)
In this paper, we identify demand shocks that can have a permanent effect on output through hysteresis effects. We call these shocks permanent demand shocks. They are found to be quantitatively important in the United States, in particular when the sample includes the Great Recession. Recessions driven by permanent demand shocks lead to a permanent decline in employment and investment, although output per worker is largely unaffected. We find strong evidence that hysteresis transmits through a rise in long-term unemployment and a decline in labor force participation and disproportionately affects the least productive workers.
Keywords: C32; E24; E32; 330; hysteresis; structural vector autoregressions; sign restrictions; long-run restrictions; employment; labor productivity; local projections